Komunikasi Inklusif dalam Pemberdayaan Penyandang Disabilitas di Roemah Difabel Indonesia - Natalia Sari Pujiastuti; Suhariyanto Suhariyanto; Agus Edy Laksono; Viro Dharma Saputra (Sahabat Akademia Group, 2026)
This study examines how inclusive communication operates within community based disability empowerment. Specifically, it explores how communication adaptation supports access to participation and relates to role changes among members at Roemah Difabel Indonesia in Semarang, Central Java. Employing a qualitative intrinsic case study approach, data was primarily collected through complete interviews with five key informants deeply involved in organizational management, facilitation, mentoring, and community activities. These interviews, supported by participant observation and organizational documentation, were analyzed thematically. The findings reveal that inclusive communication is effectively practiced through simplified language, repeated explanations, written and visual information, direct demonstrations, gestures, sign language, digital media, and tailored mentoring. These specific adaptations helped members understand information clearly and participate actively in learning, community, and productive activities. Empirical evidence shows a distinct contextual pattern where communication adaptation is strongly associated with expanded participation, increased opportunities to use acquired skills, and greater responsibility for several members. The study concludes that disability empowerment programs must integrate communication accessibility with meaningful participation and pathways for members to assume appropriate social roles. While limited by a single case focus and the lack of longitudinal assessment, the findings strongly recommend future comparative studies.